Differential distribution of sperm subpopulations and incidence of pleiomorphisms in ejaculates of captive howling monkeys (Alouatta caraya) - Valle, R. R. [UNESP]; Carvalho, F. M.; Muniz, J. A. P. C.; Leal, C. L. V.; Garcia-Herreros, M. (Springer, 2013)
The aim of this study was to develop an objective method to determine the incidence of pleiomorphisms and its influence on the distribution of sperm morphometric subpopulations in ejaculates of howling monkeys (Alouatta caraya) by using a combination of computerized analysis system (ASMA) and principal component analysis (PCA) methods. Ejaculates were collected by electroejaculation methods on a regular basis from five individuals maintained under identical captive environmental, nutritional, and management conditions. Each sperm head was measured for dimensional parameters (Area [A, (square micrometers)], Perimeter [P, (micrometers)], Length [L, (micrometers)], and Width [W, (micrometers)]) and shape-derived parameters (Ellipticity [(L/W)], Elongation [(L - W)/(L + W)], and Rugosity [(4 pi A/P-2)]). PCA revealed two principal components explaining more than the 96 % of the variance. Clustering methods and discriminant analyzes were performed and seven separate subpopulations were identified. There were differences (P < 0.001) in the distribution of the seven subpopulations as well as in the incidence of abnormal pleiomorphisms (58.6 %, 49.8 %, 35.1 %, 66.4 %, and 55.1 %, P < 0.05) among the five donors tested. Our results indicated that differences among individuals related to the incidence of pleiomorphisms, and sperm subpopulational structure was not related to the captivity conditions or the sperm collection method, since all individuals were studied under identical conditions. In conclusion, the combination of ASMA and PCA is a useful clinical diagnostic resource for detecting deficiencies in sperm morphology and sperm subpopulations in A. caraya ejaculates that could be used in ex situ conservation programs of threatened species in Alouatta genus or even other endangered neotropical primate species.
Keywords: Sperm morphometry; Principal component analysis; Sperm subpopulations; Sperm pleiomorphisms; Captive management; Alouatta caraya